No sports, no spectators - no media, no money? The importance of spectators and broadcasting for professional sports during COVID-19 - Horky, T. (Soccer & Society, 2020)
In 2020, the COVID-19 pandemic is giving sports a timeout. Due to the risk of infection, in Germany no sports events with live spectators were allowed for weeks starting on March 13. The question arises, what would be the impact on spectators and with that on live broadcasting for different sports? While professional sport leagues like handball and hockey (ice hockey) stopped, the football (soccer) league restarted games without spectators on May 16. Using two approaches of sports action as a public presentation of performance and the consumption capital theory, the share of revenues like media, spectators, sponsoring of the biggest sport leagues in Germany is compared. Following this up, the economic impact of COVID-19 on professional sports in Germany is explained. As a result games without spectators (`ghost games`), the gap between major sports and minor sports seems to be becoming larger.